Insygnia kanonickie. Aspekt prawno-liturgiczny - Adamczyk, Jerzy (Analecta Cracoviensia, 2019)
The aim of the article is to present legal and theological aspects of the insignia of the canons in the light of applicable law. The first part portrays the composition of the canons’ outfit. The second part depicts the problems of the canons’ cross and ring, and the third part is dedicated to the use of canons’ insignia. The article ends with conclusions and references.